The Genus Clonostachys (Bionectria) as a Potential Tool Against Agricultural Pest and Other Biotechnological Applications: A Review - Manuela Reyes-Estebanez; Pedro Mendoza-de Gives (Microbiology Research)
The Clonostachys genus is a saprophytic soil microfungus (Ascomycota). It exhibits significant ecological adaptability and plays a crucial role in maintaining the balance of soil microorganisms. Species within this genus are natural antagonists of insects and nematodes, and they also combat phytopathogenic fungi through mycoparasitism. This process involves producing lytic enzymes and competing for space and nutrients. Clonostachys species are effective biocontrol agents in agriculture and have been utilized to manage pests affecting many high-value commercial crops, acting as a natural biopesticide. They inhabit plant tissues, boosting plant defenses and activating genes for water and nutrient uptake, enhancing plant performance. Additionally, they produce enzymes and bioactive metabolites with antimicrobial, antifungal, nematocidal, anticancer, and antioxidant properties. Clonostachys species can degrade plastic waste and remove hydrocarbons from crude oil-contaminated sites when functioning as endophytes, positioning Clonostachys as a promising candidate for reducing environmental pollution. There are still challenges and limitations, such as the continuous surveillance of the safety of Clonostachys species on plants, the establishment of commercial applications, formulation viability, and variability due to field conditions. These issues will have to be addressed. This review provides an overview of Clonostachys ecology, morphology, classification, and biotechnological applications, emphasizing its significance in various fields.